The Accuracy of Cut-Out-Rescan Method in Digital Impression - Ally, Sabrina; Ritonga, Putri Welda Utami; Tamin , Haslinda Z. (Indonesian Journal of Prosthodontic, 2024)
The process of fabricating fixed dentures starts with an impression of the anatomical structure of the teeth. Currently, the use of an intraoral scanner (IOS) for digital impression has improved due to its rapid workflow. One of the advantages of IOS is the availability of the cut-out-rescan method, which involves rescanning unscanned areas (mesh holes) without the need to repeat the entire impression procedure. This method is recommended to assist in the digital workflow of fixed denture fabrication, by performing a cut-out on the prepared tooth, rescan, and merge it with the initial scan (pre-preparation scan). The accuracy of the cut-out-rescan method is measured based on trueness and precision. The aim of this literature is to describe the accuracy of the cut-out-rescan method in digital impression. Rescanning procedure influenced the accuracy of the definitive scan. The number and diameter of mesh holes influenced the scanning accuracy of IOS. The higher the number and diameter of the rescanned area, the lower the accuracy of the IOS. The narrow anatomical structure of teeth such as the anterior teeth also made the rescanning process more difficult. Nonetheless, the use of the cut-out-rescan method is quite practical and makes it easier for clinicians to perform digital workflow as there is no need to repeat impression procedure to obtain a definitive virtual cast. Clinical workflow becomes quicker by the elimination of physical casts, thus reducing clinical expenses. Keywords: IOS, workflow, cut-out-rescan, mesh holes, accuracy